Good governance based on Maqasid al-Shariah in management of tabung masjid: a case study of Malaysia - Zakariyah, Luqman; Mhd. Sarif, Suhaimi; Ahmad H.Osman, Rahmah; Ibrahim, Shukran (2017)
Malaysia is considered as one of the creative and vibrant Islamic countries that promote modernity and civilization of Islam in the world. Its approach to good governance, especially in Islamic banking and Finance, administration of Islamic affairs in general, and public welfare are undeniable. However, its attention to good governance in the management of Tabung Masjid is still at a developing stage. Tabung Masjid in Malaysia is still lacking good governance in many ways. Some of these ways are strategic planning for expenditure, accounting, banking, and investing the surplus of Tabung Masjid.